Openness to Changing Religious Views Is Related to Radial Diffusivity in the Genu of the Corpus Callosum in an Initial Study of Healthy Young Adults - Xu, Jiansong; McClintock, Clayton H.; Balodis, Iris M.; Miller, Lisa; Potenza, Marc N. (Frontiers in Psychology, 2018)
A quest orientation to religion is characterized by a search for answers to complex existential questions, a perception of religious doubt as positive, and an openness to change one’s religious views as one grows and changes. This orientation is inversely related to fundamentalism, authoritarianism, and prejudice and directly related to cognitive complexity, openness to experience, and prosociality. To date, the neural correlates of religious quest have not been investigated. This study assessed the relationships between measures linked to white matter integrity and quest religious orientation among 24 healthy participants using diffusion tensor imaging and the quest scale. A tract-based spatial statistical analysis whole-brain-corrected initially employing an accepted threshold (pTFCE<0.05) and then applying a Bonferroni correction (pTFCE<0.0042) identified a region of the genu of the corpus callosum as showing radial diffusivity measures being related to openness to change religious beliefs. When not employing a Bonferroni correction (pTFCE<0.05), the openness-to-change subscale of the quest scale negatively correlated with radial diffusivity and mean diffusivity measures in extensive white matter regions in both hemispheres that include the corpus callosum body, genu, and splenium, superior longitudinal fasciculus, forceps minor, external capsule, and inferior fronto-occipital fasciculus. No relationships were found with the other subscales. These findings suggest that a greater openness to change one’s religious views is associated with better white-matter integrity specifically in the genu of the corpus callosum and likely in a more extensive set of white-matter structures interconnecting widespread cortical and subcortical regions in the brain across hemispheres. They, furthermore, suggest structural similarities that may link this tendency to associated positive psychological traits, including creative cognition and post-traumatic growth.